Root adaptations to soils with low fertility and aluminium toxicity - Rao, Idupulapati M.; Miles, John W.; Beebe, Stephen E.; Horst, Walter J. (Oxford University Press, 2016)
BACKGROUND Plants depend on their root systems to acquire the water and nutrients necessary for their survival in nature, and for their yield and nutritional quality in agriculture. Root systems are complex and a variety of root phenes have been identified as contributors to adaptation to soils with low fertility and aluminium (Al) toxicity. Phenotypic characterization of root adaptations to infertile soils is enabling plant breeders to develop improved cultivars that not only yield more, but also contribute to yield stability and nutritional security in the face of climate variability.